Learning Nahwu Using the Ibtida'i Method at Madrasah Diniyah Jepara - Natsir, Muhammad; As'ad, Ali (Asalibuna, 2024)
Learning Arabic grammar and the Kitab Kuning is the main focus of madrasah diniyah and Islamic boarding school education. Hence, adapting strategies, methods, and media for learning materials is Asatidz's (teachers) main concern in motivating students' interest in participating in learning at these two institutions. The research used a quasi-experimental design to describe, analyze, and describe (1) the application of the Ibtida’i method and (2) Asatidz's perception of the application of the Ibtida’i method in Madrasah Diniyah throughout Jepara district in learning Arabic grammar and turats. This research results show that 1) the procedures and applications of the Ibtida’i method are simultaneous between mastery of grammatical rules and application in grammatical learning and the meaning of the turats. 2) Asatidz's perception of the application of the Ibtida’i method shows that a) the majority of asatidz always teach Arabic grammar (nahwu and shorof) so that it becomes their field of expertise, b) the majority of asztidz have sufficiently mastered the stages of learning using the Ibtida’i method, c) the majority of asatidz have sufficiently mastered the characteristics of the Ibtida’i method, d) the majority of asatidz are consistent in applying the Ibtida’i method, e) the majority of asatidz are quite motivated to apply the Ibtida’i method in learning Arabic Grammatical, f) the majority of students are quite enthusiastic and motivated in learning Arabic Grammatical using the Ibtida’i method on the score, g) learning Arabic Grammatical using the Ibtida’i method makes a positive contribution to achieving targets in learning Arabic Grammatical and the book of turats.